The Impact of Parenting Errors on the Formation of Children's Personality and Adaptability - Rana Putria Hikmah; Khansa Laina Asyadza; Zhilla Rahim (Inovan Publisher, 2025)
This paper examines the impact of parenting errors on the formation of children's personality and adaptability. This literature review aims to analyze the impact of parenting errors on the formation of children's personality and adaptability. A qualitative descriptive method was used to collect data through literature study. The literature reviewed in this article is a total of 4 articles found in the Obsession Journal. The research results show that mistakes in parenting, such as parenting that is too authoritarian or too permissive, can have a negative impact on the formation of a child's personality and ability to adapt to the environment. Children raised with inappropriate parenting styles may have difficulty building healthy interpersonal relationships, regulating emotions, and dealing with stress. This research highlights the need for a positive and consistent parenting approach to support healthy and optimal child development.